Subjective memory complaints in elders: depression, anxiety, or cognitive decline?. (6th December 2012) - Balash, Y.; Mordechovich, M.; Shabtai, H.; Giladi, N.; Gurevich, T.; Korczyn, A. D.
<x xml:space="preserve">Abstract</x> Objectives To study the association of subjective memory complaints (SMC) with affective state and cognitive performance in elders. Materials and methods We studied community dwelling elderly persons with normal physical examination. Participants completed questionnaires regarding memory difficulties and lifestyle habits, the Geriatric Depression Scale (GDS) and the Spielberger State‐Trait Anxiety Inventory (STAI). Depending on their answers to the question about their memory condition, participants were divided into complainers and non‐complainers and to five groups according to their MMSE scores. These data have been compared to objective cognitive performance according to Mindstreams ‐ a computerized neuropsychological battery. A logistic regression was performed to evaluate odds ratios (OR) and 95% confidence intervals (CI) for those factors, which were associated with SMС (dependent variable). Results Of 636 consecutive subjects (61% females), 507 participants (79.7%) had SMС. Presence of SMC was inversely correlated with MMSE scores, (r = −0.108; P for trend = 0.007). GDS and STAI scores were higher among subjects with SMC (OR = 1.23: CI 95%: 1.1–1.36 and OR = 1.03: CI 95%: 1.01–1.07, respectively). SMC did not correlate with objective cognitive performance measured by Mindstreams. Conclusions Subjective memory complaints are associated with sub‐syndromal depression and anxiety in healthy cognitively normal elders.